ANÁLISE DOS IMPACTOS AMBIENTAIS RELACIONADOS À VISITAÇÃO NO BURACO DO PADRE, PARQUE NACIONAL DOS CAMPOS GERAIS (PR) - Burgardt, Solange (2016)
The Campos Gerais National Park includes seven areas open to touristic activity. One of those areas is named “Buraco do Padre”. This one consists in a vertical cave, its inside access is granted by a trail of about 730 meters. For its scenic beauty, its importance in the regional history and culture, moreover his geological, biological and tourism aspects, its already part of the environmental protected areas created before the National Park, however, the visitation methods was never particularly meant to reduce the environmental impact or even to considerate the guidance of the competent entities. The landholding situation of this National Park is in process, witch means, the protect area is not established yet and the visitation areas are still private property. Considering the lack of control in the touristic history of the Park, the meaning of this work is to analyze the environment impact produced in the main trail of the “Buraco do Padre”, aiming to create control methods that reduce the negative impacts occurring in the actual touristic activity. To achieve this goal, sample points were selected along the trail that gives access to the cave witch, every month, in the period of one year, some environmental impact indicators were observed. Additional to the main goal, a study on the trail was made to categorize it, according to its function, difficulty level, physical requirements, terrain declivity and distance. Besides that, the segments of the trail that demands more attention were identified, for priority handling an intervention. The data resulting from this research can be used for interventions in a short, medium and long term, granting the public access to the area within the parameter of environmental protection fulfilling the Campos Gerais National Park creation purpose. Some short-term actions can be directed to the basic aintenance of the trail, as coverage of secondary trails and detours with litter the area itself and containment booms erosion points; medium-term actions can be directed to the incorporation of more elaborate structures such as elevated walkways points of puddling, or bridges in the areas where they spend water bodies and long-term actions can be directed at environmental awareness of visitors with the intention of making that the behavior of this is geared towards conservation of the visited area.